Atmospheric neutrinos with the first detection units of KM3NeT/ARCA. (29th November 2021) - Sinopoulou, A.; Coniglione, R.; Muller, R.; Tzamariudaki, E.
Abstract: The KM3NeT collaboration is constructing two deep-sea Cherenkov detectors in the Mediterranean Sea. The ARCA detector aims at TeV-PeV neutrino astronomy, while the ORCA detector is optimised for atmospheric neutrino oscillation studies at energies of a few GeV. In this contribution, an analysis of the data collected with the first deployed detection units of the ARCA detector is presented. A high-purity sample of atmospheric neutrinos is selected demonstrating the capability of the ARCA detector.